Productivity assessment of alternative timber debarking methods - Gulci, Neşe; Akay, Abdullah Emin; Erdaş, Orhan (Hrvatsko Sumarsko Drustvo, 2017)
In Turkey, timber debarking stages are generally carried out by using axes. However, this method takes a lot of time and requires more work forces. In addition, since leaving residual trees with bark in stands increases the risk of insect damages, residual trees require quick barking process. In recent years, chainsaw mounted debarking tools have been widely used in debarking stages due to performing jobs quicker with less labor force. In this study, two different debarking methods including using axes and debarking tool were analyzed by considering operation productivity. The field studies were conducted in Brutian Pine (Pinus brutia Ten.) stand located in Bahçe Forest Enterprise Chief of Osmaniye Forest Enterprise Directorate in Adana Regional Forestry Directorate. As a result of study, the productivity of chainsaw mounted debarking tool was found to be five times higher than that of using axes for debarking. Thus, use of chainsaw mounted debarking tool is better alternative than use of axe in debarking activities, as it takes less time and minimize physical work load of the loggers.
Keywords: Chainsaw mounted debarking tool; Debarking activity; Debarking productivity; Forest operations